Evaluating the safety and efficacy of Lacticaseibacillus paracasei TISTR 2593 as a therapeutic probiotic for obesity prevention - Sitdhipol, Jaruwan; Niwasabutra, Kanidta; Chaiyawan, Neungnut; Nuankham, Kamonsri; Thanagornyothin, Thanaphol; Tanasupawat, Somboon; Chanput, Wasaporn Preteseille; Phapugrangkul, Pongsathon; Chaipanya, Chaivarakun; Phuengjayaem, Sukanya; Poothong, Saranporn; Kingkaew, Engkarat (Frontiers in Microbiology, 2025)
Several recent studies have reported the potential of probiotics in reducing body weight and fat mass and improving glucose and lipid metabolism. Therefore, probiotic administration is considered an alternative approach for treating obesity. The objective of this study was to evaluate the probiotic properties and antiadipogenic potential of the strain TISTR 2593. Through whole-genome sequence analysis, the strain TISTR 2593 was identified as Lacticaseibacillus paracasei. L. paracasei TISTR 2593 exhibited γ-hemolytic activity (nonhemolysis) and demonstrated susceptibility to antibiotics, indicating that it is generally safe for consumption. Additionally, this strain displayed desirable probiotic properties, including tolerance to artificial gastric juice and bile salts, adhesion to Caco-2 cells, and the ability to inhibit pathogens. Furthermore, L. paracasei TISTR 2593 exhibited cholesterol-reducing capability and demonstrated antiadipogenic activity. In 3T3-L1 adipocytes, treatment with 10% (w/v) heated L. paracasei TISTR 2593 cells resulted in an approximately 50% reduction in lipid accumulation, similar to the positive control (quercetin). Moreover, L. paracasei TISTR 2593 heat-killed cells dose-dependently decreased the expression levels of CCAAT/enhancer-binding protein-α and peroxisome proliferator-activated receptor-γ, two vital transcription factors involved in the early stage of adipocyte differentiation. These findings suggest that L. paracasei TISTR 2593 possesses probiotic and functional properties, including antiadipogenic activity, supporting its potential as a therapeutic probiotic supplement for preventing obesity. Overall, the results of this study indicate that L. paracasei TISTR 2593 exhibits promising probiotic characteristics and beneficial effects on adipogenesis modulation, reinforcing its potential as a therapeutic option in obesity prevention.